Adulta femenina de 60 años con hipertensión arterial estadio l y sobrepeso - Carrasco Moreno, Jeniffer Joan (2019)
Arterial hypertension is a no transmittable chronic disease that is cha determines by a constant rise in blood pressure that can vary from one individual to another depending on age and weight. Being overweight is an issue affecting millions of people in Latin America and in Ecuador. The present case study is based on a female patient of 60 years , with two daughters, live in Babahoyo and who was diagnosed with stage l hypertension about 7 years age , goes to the outpatient clinic due to dizziness , white spots in skin tiredness and headache . One of the objectives that was proposed in the case study was to design a nutritional plan according to the pathology of the patient, where the nutritional assessment was made and was determined through the body mass index that is overweight was made to the patient biochemical tests finding high cholesterol. Through the intervention, the patient obtained favorable for her health by normalizing her blood pressure and avoiding future complications. The patient is cited 3 months decreasing 6 kg with an IMC 24. 8 kg / mm 2 obtaining favorable results with weight. A hyposodic and hypoglycemic diet was designed, modifying its alimentary habits with the intake 1382 kilocalories covering the nutritional requirements of the patient according to his pathology.